Idarubicin plus BuCy versus BuCy conditioning regimens for intermediate‐risk acute myeloid leukemia in first complete remission undergoing auto‐HSCT: An open‐label, multicenter, randomized phase 3 trial. Issue 3 (1st January 2023) - Liu, Hui; Huang, Fen; Zhang, Yu; Wu, Meiqing; Xu, Na; Fan, Zhiping; Sun, Zhiqiang; Li, Xudong; Lin, Dongjun; Xiong, Yiying; Liu, Xiaodan; Lin, Ren; et al.
Abstract: We report a randomized prospective phase 3 study, designed to evaluate the efficacy and tolerability of idarubicin plus busulfan and cyclophosphamide (IDA‐BuCy) versus BuCy in autologous hematopoietic stem‐cell transplantation (auto‐HSCT) for intermediate‐risk acute myeloid leukemia (IR‐AML) patients in first complete remission (CR1). One hundred and fifty‐four patients were enrolled and randomized to receive IDA‐BuCy (IDA 15 mg/m2/day on days −12 to −10, Bu 3.2 mg/kg/day on days −7 to −4, and Cy 60 mg/kg/day on days −3 to −2) or BuCy. The 2‐year incidence of relapse was 15.6% and 19.5% in IDA‐BuCy and BuCy groups ( p = 0.482), respectively. There was no significant overall survival (OS) and disease‐free survival (DFS) benefit for IR‐AML patients receiving IDA‐BuCy (2‐year OS 81.8% in IDA‐BuCy vs. 83.1% in BuCy, p = 0.798; 2‐year DFS 76.6% in IDA‐BuCy vs. 79.2% in BuCy, p = 0.693). Grade 3 or worse regimen‐related toxicity (RRT) was reported for 22 (28.9%) of 76 and 9 (12.0%) of 75 patients in two groups ( p = 0.015), respectively. AEs within 100 days with an outcome of death were reported for 4 (5.3%) and 0 patients in two groups. In conclusion, IDA‐BuCy has higher RRT and similar anti‐leukemic activity compared with BuCy in IR‐AML patients in CR1 undergoing auto‐HSCT. Thus, caution should be taken when choosing IDA‐BuCy for IR‐AML patients in CR1 with auto‐HSCT. This trial is registered with ClinicalTrials.gov, NCT02671708, and is complete.